Spontaneous coronary artery dissection: current evidence from cardiac magnetic resonance and angiography screening. (3rd October 2022) - Androulakis, E; Azzu, A; Papagkikas, P; Antonopoulos, A; Al-Hussaini, A; Pennell, D; Mohiaddin, R
Abstract: Purpose: To assess the distribution and extent of myocardial infarction, as well as possible clinical significance of peripheral arteriopathy screening in a cohort of patients presented with spontaneous coronary dissection (SCAD) using cardiovascular magnetic resonance (CMR) for cardiac and vascular imaging. The adverse CMR features and predictors of infarction in subgroup analysis were also investigated. Methods: This is an observational, single centre study of 144 consecutive, angiographically confirmed SCAD survivors >18 years old, based on collected data from Jan 2008-Nov 2020. All scans were performed on a 1.5-Tesla scanner. Cardiac structural and functional indices, myocardial infarct size and distribution were evaluated. In addition, vascular imaging was performed in all patients for thoracic aorta screening as part of the routine protocol, and in 75 patients peripheral arteriopathy screening from Circle of Willis to the iliac arteries was performed using 2D multi-slice and cine imaging, as well as 3D imaging methods. Results: In the total population, 64% had infarction. Infarct size (%) was predictive of reduced left ventricular ejection fraction (LVEF) (p<0.001) and increased diastolic volumes (p<0.001 for both). Logistic regression showed SCAD in right coronary artery (Odds Ratio (OR): 5.2, p=0.034) predicted the presence of infarction. In the group who also underwent peripheral vascular screening, the overall prevalence of extra-coronary arteriopathy was 27% with fibromuscular dysplasia accounting for one-fourth of the cases (Figure 1). Of note, most positive vascular screening patients (73.3%) exhibited infarction (OR: 7.0, p=0.041), distributed in more than one territory (OR: 4.0, p=0.015) (Figure 2), while infarct size was negatively correlated with LVEF (p<0.001). Right ventricular ejection fraction was significantly reduced in positive screening patients (58.8±7.4 vs. 63.0±8.0, p=0.045). Further subgroup analysis showed pregnancy associated SCAD patients had significantly larger sized infarcts (25.1±6.1 vs. 6.2±0.7%, p<0.001) with reduced LVEF (51.0 vs 63.6±7.6, p<0.001). In logistic regression, this condition also predicted large infarcts >10% (OR: 9.8, p=0.009) in anterior walls (p<0.001). Conclusions: Patients with SCAD require careful assessment of myocardial structure, function and characterization of infarction which may reflect the underlying pathophysiology. Extra coronary vascular screening, although not established in clinical practice, seems a rational strategy to potentially identify a subgroup with more severe infarction and likely to have vascular pathology. Funding Acknowledgement: Type of funding sources: None.